#TITLE_ALTERNATIVE# - HERLAMBANG (NIM 12206003); Pembimbing: Dr. Ir. Taufan Marhaendrajana ,M.Sc., BASKORO
XA Field is a marginal field because it has a small IOIP. This field began production in July 1997 with the operation of wells XA-01 and closed in February 1998 because of large amounts of water produced beyond economics limit. Oil price increase significantly, making the management held a study to reactivate this field. This study covers the development of a reservoir model and reservoir simulation. Before doing reservoir modeling , first we have to build reservoir characterization and reservoir fluid analysis. Furthermore, after the modeling is finished, reservoir engineer conduct history matching. History matching is done to validate the model which was created. Finally we are doing reservoir simulations to determine which scenario gives most optimum field development. The scenario selected in this field is to conduct an infill drilling. In XA field reservoir simulation, we conducted sensitivity to nine wells of different positions with three different rate constraints.